Rule of Law: Its Impact on Quality of Life (European Journal of Interdisciplinary Studies, 2016)
Quality of life has very much to do with justice. Even though justice is hard to define but the basic idea remains that what is right is good and what is oppressive, is bad. So applying the same formula to all set of circumstances be it economy, social, and politics, will invigorate justice. The failure of world monetary system due to the crave for money and power has led the seekers to abuse and oppress the weaklings. The govt, financial institutions and commercial industries are no exception. Since justice is seen as obstacles to fast money and power, accountability have been regarded as a nuisance and justice is sidestepped and suppressed. Notion of Rule of Law emerge due to the need to address all these wrongdoings. Thus this paper seeks to discuss the problem underlying the situation and the means of overcoming it. One way is by imposing accountability and Rule of Law. Closely related to this issue too is the quality of life. Despite the increase standard of living; we still witnessed the glaring economic disparity between the rich and poor countries. Do this indicator project better living standard? Or it is measured from the view of the rich and the elite only? Hence this paper seeks to discuss that to implement justice there must be distribution of wealth and resources. What sensible person would deem as right, thus good. Apart from the western system that promotes Rule of Law, what is just and unjust has been clearly underlined by Islam. Man become just when they are able to restrict themselves from oppressing and tormenting others and Islam provide complete guidance to the existing crisis we faced now. Nevertheless we saw failures everywhere. They are due to the refusal of the followers to follow it, not the fault of the religion. It is attributed by their ignorance. This paper is important to show economy and social as well as quality of life devoid of justice stemming from manipulative capitalism and greed, are unsustainable and destructive. Unless and until this is understood, economic, political, environmental and social imbalances will never subside.